A summary of the Clinical Practice Guideline for the Diagnosis and Management of Voice Disorders, 2018 in Japan. Issue 1 (February 2020) - Umeno, Hirohito; Hyodo, Masamitsu; Haji, Tomoyuki; Hara, Hirotaka; Imaizumi, Mitsuyoshi; Ishige, Miyoko; Kumada, Masanobu; Makiyama, Kiyoshi; Nishizawa, Noriko; Saito, Koichiro; Shiromoto, Osamu; Suehiro, Atsushi; et al.
Abstract: Objective: To develop a summary of the first version of the Clinical Practice Guideline of Voice Disorders for Diagnosis, Management, and Treatment in Japan by the Clinical Practice Guideline Committee of the Japan Society of Logopedics and Phoniatrics and The Japan Laryngological Association. The 2018 recommendations, based on a review of the scientific literature, are intended to serve as clinical practice guidelines for the diagnosis, management, and treatment of voice disorders in Japan. Methods: A summary of the original version of the Clinical Practice Guideline of Voice Disorders for Diagnosis, Management, and Treatment in Japan was described. Recommendations for the diagnosis, management, and treatment of voice disorders were prepared. Twelve clinical questions (CQs) regarding the diagnosis, management, treatment, and effectiveness of therapy for voice disorders were also prepared. Results: A summary of the first version of the clinical practice guidelines for the diagnosis, management, and therapy of voice disorders was prepared and is presented. Additionally, answers to the 12 CQs on the diagnosis, management, treatment, and effectiveness of voice disorder therapy were prepared, and include evidence-based recommendations. Conclusion: These guidelines present a summary of the standard approaches for the diagnosis and treatment of voice disorders and relevant CQs that consider the medical environments in Japan. We hope that the guidelines will assist physicians in clinical settings for patients with voice disorders.